The Influence Of Student Self-Management On The Learning Outcomes Of Eighth Grade Students At Pondok Pesantren Darus Sholihin - Nasution, Ummutu Sakdiah; Siregar, Sakinah Ubudiyah; Hasibuan, Lily Rohanita (UNIVERSITAS PAKUAN, 2017)
This research aims to determine the influence of students' self-management on the learning outcomes of eighth-grade students at Pondok Pesantren Darus Sholihin. Self-management refers to an individual's ability to regulate emotions, time, and behavior in achieving specific goals, particularly in an academic context. This type of research is an Ex Post Facto study with a quantitative approach. The sample of this study consists of 25 students from class VIII A Pondok Pesantren Darus Shalihin Labuhanbatu, determined using the Cluster Random Sampling technique. The data for this research were collected using two instruments: a self-management questionnaire and students' academic mathematics scores as indicators of learning outcomes. The results of this study used a Simple Linear Regression Test which showed a significance level of 0.000. This means that the significance level of the research is less than the significance level of 0.05. Thus, self-management significantly positively affects students' learning outcomes. Keywords: Self-Management. Learning Outcomes